Resiliência face à pandemia COVID-19 em atletas federados/as portugueses/as: estudo exploratório - Inês de Santos Vazquez (2021)
COVID-19 triggered the greatest global state of emergency that humanity has experienced since World War II, constituting a long-lasting and challenging period of transition in anyone's life and career. In the case of federated athletes, some specific challenges arise, especially those associated with the restrictions in training and competitions imposed by health measures. These athletes were the ones who came to an early standstill and then picked up again later. The main objective of this exploratory and cross-sectional study is to understand the resilience in federated athletes in the face of the aforementioned adversity. 1016 athletes participated in this research with a mean age of 30 years (M=29.7; SD=12.5), ranging from 18 to 83 years, mostly male (55.4%) and with an average of 14 years of federated practice (M=14.2; SD=9.55). Due to the implementation of the second mandatory confinement in January 2021, athletes are also categorized according to the time of response - before the 2nd confinement (G1) and during the 2nd confinement (G2). Data was collected between December 2020 and March 2021 through an online questionnaire. Resilience was measured through a tripartite assessment of its domains: risk factors (personal experience with the virus, effects on sports practice, and fear of COVID-19), protection mechanisms (satisfaction with social support and coping strategies), and adjustment (life satisfaction, positive and negative affect, and subjective impact of the pandemic). The results suggest that the drop in training characteristics, time without training and in confinement, fear of COVID-19, and the use of behavioral divestment strategies are negative predictors of positive adjustment. On the other hand, active coping, humor, and satisfaction with social support positively predicted athletes' adaptation. Furthermore, it was found that being female is an additional risk factor and that external circumstances, such as the severity of the pandemic, seem to interfere with the participants' adjustment. It is concluded that athletes can mitigate the impact of this adversity by looking for the positive aspects of the situation, making active efforts to cope with it, facing it with a sense of humor, and fostering social contacts. In addition, it is suggested that sports institutions should prioritize athletes' mental health and enable their sports practice as much as possible.